Tactical styles of fighting and functional asymmetry of the brain among elite wrestlers - Korobeinikova, L.; Korobeynikov.G.; Cynarski, W. J.; Borysova, O.; Kovalchuk, V.; Matveev, S.; Vorontsov, A.; Novak, V. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Purpose - to investigate the relationship between functional brain asymmetry and tactical competition strategies among elite level wrestlers. Methods. Examination of thirty elite athletes (Ukrainian Greco-Roman National Team members), aged between 20 and 28. In order to determine the dominance of cerebral hemisphere, the dependence assessment test was used (test version «Color & Word Test»; J.R. Stroop, 1935). Level of psycho-emotional stability (stress resistance) and functional mobility of nerve processes was determined in accordance with the results of the psycho diagnostical complex «Multipsychometr-05». Statistical analysis of data was conducted by using the «Statistica 6» software package using methods of non-parametric statistics. Results. The results found that an offensive style of wrestling among elite level wrestlers is related to the presence of brain hemisphere symmetry (p<0,05), field independence from external stimuli (p<0,05), high stress resistance (p<0,05) and high speeds of perception and of processing information (p<0,05). A defensive style of wrestling among elite level wrestlers is characterized by functional brain asymmetry with dominance of the right hemisphere (p<0,05), filed dependence from external stimuli and high throughput neurodynamic processes capacity (p<0,05). The combined style of wrestling among elite level athletes is characterized by functional brain symmetry and field independence from external stimuli (p<0,05). At the same time, the combined style indicates lower level of stress resistance (p<0,05), combined with emotional stability and optimal lability of nervous system (p<0,05). Conclusions. Interconnection between styles of fighting among elite level wrestlers and characteristics of functional brain asymmetry was identified.